Constitutional Thought of Abu Al-Hasan Al-Mawardi in Political Islam - Mohamad Latif; Ahmad Hisyam Syamil; Amir Reza Kusuma; Iqbal Maulana Alfianysyah (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
The Western thinkers believe that Muslim scholars were the pioneers of philosophical thought ethics, yet provided no significant contribution to the field of political thought. Furthermore, the former treats the latter as possessing no clear views on political thought and that religion and Islamic civilization have by no means political thought. This point of view is faulty since the sixteen and seventeenth centuries. Europe failed to acknowledge the character of Muslim political thought. Al-Mawardi was one of the Muslim thinkers who came forward to construct an attractive paradigmatic contribution between social concepts or systems with institutions (state).